Competition and yield performance in mixtures of oats and barley - nitrogen fertilization, density and proportion of the components - Jokinen, Kari (Agricultural and Food Science, 1991)
Competition and yield performance in mixtures of barley and oats were evaluated from addition series experiments (three experiments) in 1983 and in 1984. Three doses of nitrogen fertilization (10 kgN/ha, 40 kgN/ha and 80 kgN/ha) were applied. In the first year the components were Agneta barley and Veli oats and in 1984in addition to the previous combination also Ida barley and Veli oats were included. The competitive relationship between components was analysed by replacement series model and by regression analysis. The results showed that the dominant component according to the regression analysis was also dominant according to the indices of the replacement series model independently of density and proportion. Barley was generally more competitive than oats. The dominance of barley usually increased with increasing nitrogen fertilization, especially in the mixture of Agneta and Veli. All the yield components of the barley plants increased with the decreasing proportion of barley in the mixture. In 1983, some mixtures overyielded significantly (p<0.05). The relative yield total being usually greater than one indicated yield advantage. In 1984, oats suffered from insect damage and neither barley cultivar was able to compensate enough so no overyielding occurred. The relative yield total was lower than one and thus no yield advantage was achieved.